2016
DOI: 10.3126/jnbs.v9i1.14598
|View full text |Cite
|
Sign up to set email alerts
|

Quality Management: An Effective Approach to Success

Abstract: Product quality has entered the consciousness of organizations with a vengeance. It has become crystal clear that high-quality products have a distinct advantage in the market place, that market share can be gained or lost over the quality issue. Therefore, quality is a competitive priority. Quality is the only factor that ensures an organization's survival and growth. Quality focuses on meeting consumer need, meeting the competition, improving continuously and extending these concerns to all phases of busines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…The essential characteristics of the factors utilized in determining the pattern of a housing project must reflect the long-term quality and viability of the project's housing. These factors must drive competitiveness and demonstrate the sustainability of the organization, leading to profitability for entrepreneurs and enhancing the benefits for residents (Budhathoki, 2015;Zhang et al, 2018). The literature review revealed that the suitability of the house type for residents is a key factor in building their confidence in their purchase, thereby serving as a guarantee of the house's quality (Moghayedi et al, 2021;Torbica & Stroh, 2000).…”
Section: Factors Affecting Patterns Of Housing Development Projectsmentioning
confidence: 99%
“…The essential characteristics of the factors utilized in determining the pattern of a housing project must reflect the long-term quality and viability of the project's housing. These factors must drive competitiveness and demonstrate the sustainability of the organization, leading to profitability for entrepreneurs and enhancing the benefits for residents (Budhathoki, 2015;Zhang et al, 2018). The literature review revealed that the suitability of the house type for residents is a key factor in building their confidence in their purchase, thereby serving as a guarantee of the house's quality (Moghayedi et al, 2021;Torbica & Stroh, 2000).…”
Section: Factors Affecting Patterns Of Housing Development Projectsmentioning
confidence: 99%